Textbook of diabetes and pregnancy - De Leiva, Alberto; Di Renzo, G. C. (Gian Carlo); Hod, Moshe; Jovanovic, Lois; Langer, Oded (Series in maternal-fetal medicine, 2016)
Fully updated and revised, this book contains new chapters on genetics and congenital anomalies. It provides a comprehensive, authoritative view of these difficult pregnancies and will be invaluable to maternal-fetal medicine specialists, diabetologists, neonatologists, and basic scientists working in the field.